Effects of the Amazonian essential oils of Citrus limon and Cymbopogon citratus on the growth of phytopathogenic fungi - Scalvenzi Foglia, Laura (2016)
The effect of Amazonian essential oils extracted from Citrus limon and Cymbopogon citratus was evaluated in vitro on the following phytopatogen fungi: Rhizopus stolonifer (ATCC 6227), Aspergillus oryzae (ATCC 10124), Cladosporium cladosporioides (ATCC 16022), Fusarium solani (ATCC 36031), Moniliophthora roreri and Phytophthora sp. The antifungal activity of essential oils was determined by agar diffusion method, on five different concentrations (10, 50, 100, 200, 500 µL/mL). C. citratus essential oil showed a significant antifungal activity (p<0.05), dependent on the dose. A. oryzae, C. cladosporioides, F. solani, M. roreri and R. stolonifer achieved a growth inhibition of 95%, at the maximum essential oil concentration (500 µL/mL), showing behaviour similar to the control (Thymus vulgaris). C. cladosporioides revealed a special sensibility toward C. citratus essential oil. Actually, it showed an increasing inhibition (60% to 95%), from minimum to maximum concentration respectively (10-500 µL/mL). C. limon essential oil did not exhibit a significant antifungal activity, even if C. cladosporioides growth was inhibited at 70% and F. solani growth at 72%, both at the maximum concentration (500 µL/mL). According to the obtained data, C. citratus essential oil is considered as promissory for in vitro biological control of phytopatogen fungi, while C. limon essential oil showed interesting results only for two of the studied species.